Pediatric Airway Pathology - Vijayasekaran, Shyan (Frontiers in Pediatrics, 2020)
Pediatric airway disorders may be congenital or acquired and may involve the upper, lower, or entire airway, with obstruction being a com¬mon feature. The differences between neonatal, pediatric and adult airway anatomy and physiology are important. Infants are not merely small adults in this respect and size, surface area, proportion, resistance, and compliance vary greatly between the age groups. A clear understanding of these differences and how they affect patients dependent on age is key to appropriate management.